Pengaruh Konflik Kerja Terhadap KIinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari - Virona Endila (Faculty of Social Science, Universitas Negeri Padang, 2020)
This study aimed to determine the effect of work conflict on the performance of nagari apparatus in village financial management in several villages (nagari) of Limapuluh Kota District, especially in Situjuah Limo Nagari and Mungka Sub-Districts. This research was conducted because of indications of conflict that occurred in the two Sub-Districts related to nagari financial management. The method used in this study was a quantitative method with associative model. The population in this study were all nagari apparatus in Limapuluh Kota District, totaling 75 respondents. The sample in this study consisted of 63 nagari apparatus determined using the Slovin formula with a 5% error rate and the use of Multi Stage Random Sampling techniques. Data in this study were collected through questionnaires distributed to respondents with Likert scale measurements. The data are then analyzed using multiple linear regression. The results of the study showed that the effect of the functional sub-variables of work conflict on performance was around 11.5%; and this functional work conflict has a significant influence on the performance of nagari apparatus in managing nagari finances. While the dysfunctional work conflict sub-variables have an influence of 3.5%; and this dysfunctional work conflicts do not have a significant effect on the performance of nagari apparatus. But overall, work conflict had a significant effect with a value of 17.7%, and this work conflict had a significant influence on the performance of nagari apparatus in managing nagari (village) finance.